(untitled) (International Journal of Medical and Surgical Sciences, 2016)
Neurocysticercosis (NCC) is the most common parasitic disease of the brain, has a wide variety of patterns of presentation and can mimic many diseases. We report a patient with inflammatory aneurysm, and found only 5 cases reported in the literature, and only one has histopathological report. This is a case report of a patient with diabetes and arterial hypertension condition which started with sim- plesecondarygeneralizedpartialseizures. Thestudy reported the patient was diagnosed with neurocysticercosis racemosa, resection of lesions was performed with secondary inflammatory rupture intraoperative aneurysm clipping successful NCC, inflammatory changes in the literature described in the aneurysm wall and the dependent artery, secondary to immune process with vasculitis associated with a chronic inflammatory process, these changes in the aneurysm wall increase the possibility of intraoperative rupture. Histopathological report was conclusive with neurocysticercosis.